2021
DOI: 10.3390/ijerph182111308
|View full text |Cite
|
Sign up to set email alerts
|

Adherence to Oral Contraception in Young Women: Beliefs, Locus of Control, and Psychological Reactance

Abstract: Background: There is a high dropout rate of oral contraceptive pills (OCP), mainly due to a lack of adherence to treatment. The aim of this study was to identify the psychological processes and attitudes toward medication involved in adherence to OCP, depending on the prescription, to avoid unintended pregnancies (AUP) or gynecological problems (GP). Methods: This cross-sectional study was conducted by asking 689 young women in the fertile period, mean age 23.41 (SD = 5.90), to complete questionnaires related … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 53 publications
0
8
0
Order By: Relevance
“…Although IUCD is represented as one of the most effective birth control options, it is still less commonly used compared with less effective methods including pills and condoms [11] .…”
Section: Discussionmentioning
confidence: 99%
“…Although IUCD is represented as one of the most effective birth control options, it is still less commonly used compared with less effective methods including pills and condoms [11] .…”
Section: Discussionmentioning
confidence: 99%
“…Almost one-third of the study participants reported being affected by the rising OCPs' prices, where some of them could not afford the price and were forced to search for cheaper alternative brands or to discontinue taking OCPs. Such behavior may threaten women's reproductive health and expose them to unplanned pregnancies [49,50]. Therefore, a judicious strategy should be implemented in Lebanon to rein in out-of-control drug prices and address the drug shortages that are putting a tremendous strain on the healthcare system and patient care.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies reported some delay in return to fertility in OCs users. However, it was temporary and limited to the early few months of discontinuation [4]. Moreover, the return to fertility in women who were using OCs, both cyclic and continuous, was comparable to other methods of contraception [4].…”
Section: Return To Fertilitymentioning
confidence: 98%
“…However, it was temporary and limited to the early few months of discontinuation [4]. Moreover, the return to fertility in women who were using OCs, both cyclic and continuous, was comparable to other methods of contraception [4]. Women returned to normal menses or got pregnant within the duration of 1 year [23,24] The usage of antibiotics with HC Some studies found that antibiotics usage (other than Rifampin) is associated with decreased effect of OCs [23].…”
Section: Return To Fertilitymentioning
confidence: 99%
See 1 more Smart Citation